2016
DOI: 10.1159/000447812
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinases and Hypoxic/Ischemic Nephropathy

Abstract: Tissue hypoxia/ischemia is a pathological feature of many human disorders including stroke, myocardial infarction, hypoxic/ischemic nephropathy, as well as cancer. In the kidney, the combination of limited oxygen supply to the tissues and high oxygen demand is considered the main reason for the susceptibility of the kidney to hypoxic/ischemic injury. In recent years, increasing evidence has indicated that a reduction in renal oxygen tension/blood supply plays an important role in acute kidney injury, chronic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 128 publications
4
29
0
2
Order By: Relevance
“…Consistent with our results, in a recent elegant study, Chen et al shows that miR-30a-5p expression is restricted and the reduced expression of mir-30a-5p promotes ccRCC prognosis [31]. Von Hippel-Lindau gene (VHL) has been reported as a tumor-suppressor gene, which is associated with ccRCC [32, 33]. Mathew et al has found that miR-30a-3p is repressed in the VHL deficient ccRCC tumors [34].…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with our results, in a recent elegant study, Chen et al shows that miR-30a-5p expression is restricted and the reduced expression of mir-30a-5p promotes ccRCC prognosis [31]. Von Hippel-Lindau gene (VHL) has been reported as a tumor-suppressor gene, which is associated with ccRCC [32, 33]. Mathew et al has found that miR-30a-3p is repressed in the VHL deficient ccRCC tumors [34].…”
Section: Discussionsupporting
confidence: 88%
“…The PTEN/PI3K/AKT pathway regulates multiple cellular functions, including cell growth, differentiation, proliferation, survival, motility, invasion and intracellular trafficking [27, 28]. To explore the mechanisms of inhibition of PTEN activity in the pathogenesis of IR-induced post renal fibrosis, we examined whether bpv affected the protein expression of PI3K and phosphorylation of Akt (s473) at 7 days after IR treatment.…”
Section: Resultsmentioning
confidence: 99%
“…CIAKI is also associated with replacement therapy, prolonged hospitalization, increased medical cost and increased mortality [4, 5]. The factors contributed to the pathophysiology of CIAKI are still under controversy, but primarily involve the tubular toxicity, microvascular alteration, oxidative stress, inflammation and tubular obstruction [4, 6-8]. Among these factors, inflammatory damage may be regarded as one of the most crucial factors in the development of CIAKI.…”
Section: Introductionmentioning
confidence: 99%